(untitled) (Academia Science Repository, 2023)
dialektik the stage consists of four mutually related in the article "innovative thinking" and the innovative thinking of the concept of the mechanism of the formation of the modern teacher provides. Teachers ’ innovative thinking ability educational, professional, the formation of social experience, as well as a self-nurturing and self-development are considered on the basis of.